Investigation of a solvent-cast organogel to form a liquid-gel microinterface array for electrochemical detection of lysozyme - Felisilda, Bren; Alvarez De Eulate, Eva; Arrigan, Damien (Elsevier, 2015)
Ion transfer at aqueous-organogel interfaces enables the non-redox detection of ions and ionisable species by voltammetry. In this study, a non-thermal method for preparation of an organogel was employed and used for the detection of hen-egg-white-lysozyme (HEWL) via adsorptive stripping voltammetry at an array of aqueous-organogel microinterfaces. Tetrahydrofuran solvent casting was employed to prepare the organogel mixture, hence removing the need for heating of the solution to be gelled, as used in previous studies. Cyclic voltammetry of HEWL at the microinterface array revealed a broad adsorption process on the forward scan, at positive applied potentials, followed by a desorption peak at ca. 0.68 V, indicating the detection of HEWL in this region. Application of an adsorption step, where a constant optimized potential of 0.95 V was applied, followed by voltammetric detection provided for a linear response range of 0.02-0.84 μM and a detection limit of 0.030 μM for 300 s adsorption. The detection limit was further improved by utilizing differential pulse stripping voltammetry, resulting in detection limits of 0.017 μM, 0.014 μM, and 0.010 μM for adsorptive pre-concentration times of 60, 120 and 300 s, respectively, in unstirred solutions. These results are an improvement over other methods for the detection of HEWL at aqueous-organic interfaces and offers a basis for the label-free detection of protein.